SILO’s Program: A Sociological Review Of Women's Empowerment And Education - Puja Afwanda Mayako; Yupi Sasmita Dewi Dewi; Amalia Rahmadani Ilham; Ryndian Gusti; Roby Hadi Putra Putra (Jurnal Administrasi Politik dan Sosial, 2026)
This study aimsto analyze the impact of the Sawahlunto Exemplary Wife School Program (SILO) on women's empowerment, particularly in Talawi Mudiak Village, through a sociological perspective. The SILO program has been implemented since 2022 with the goal of providing training to women who are wives and mothers to enhance their roles within the family and society. A qualitative approach with a descriptive method was used to explore the experiences of participants, consisting of 15 married women who participated in this program. Data were collected through interviews, observations, and documentation, which were then analyzed using thematic analysis techniques. The results of the study indicate that, although the program has had a positive impact on participants' understanding of family communication, household roles, and social empowerment, some challenges, such as participant absenteeism and the use of outdated modules, posed difficulties in the program's implementation. Overall, the SILO program has contributed to improving the quality of family relationships and women's empowerment in the village. This study also provides recommendations to update the modules and the participant recruitment system to optimize the program in the future